Analisis Pariwisata Berkelanjutan Terhadap Sosial, Ekonomi Dan Lingkungan Masyarakat Di Tempat Wisata Tebing Keraton Bandung - Mochamad Thoriq Althof; Dadan Ramdani (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the impact of sustainable tourism on the social, economic, and environmental aspects of the community in the Tebing Keraton tourist area, Bandung. As a popular natural tourist destination since 2014, Tebing Keraton has experienced rapid growth due to increased social media exposure. This study used a qualitative approach using in-depth interviews with five tourists and one local resident as informants. The results indicate that socially, the local community is perceived as friendly and has a positive attitude towards tourists, creating a harmonious relationship between residents and visitors. From an economic perspective, this tourism has also opened up business opportunities and increased community income, although the distribution is not yet equitable. Meanwhile, from an environmental perspective, some tourists consider the area to be not yet completely clean, but the natural environment is still relatively well preserved. A significant problem arises from the minimal involvement of the local community in tourism management, as expressed by a local community leader, Abah Ase, who feels marginalized despite being the founder of Tebing Keraton. He also highlighted changes in operating hours, which have resulted in a decline in tourist numbers and community income. This research emphasizes the importance of collaboration between the government, managers, and the community in realizing sustainable tourism that prioritizes not only economic growth but also environmental preservation and social justice. Participatory and inclusive strategies are needed, including through the role of Village-Owned Enterprises (BUMDes), to ensure that the benefits of tourism are fully felt by the local community.